APOIO FAMILIAR COMO FATOR DETERMINANTE NO DESENVOLVIMENTO NEUROPSICOMOTOR NA SÍNDROME DE DOWN (REMUNOM, 2025)
Down syndrome is a genetic alteration resulting from trisomy of chromosome 21 and is associated with delays in motor development, muscle hypotonia, postural alterations, and difficulties in body control. This study aimed to analyze the physiotherapeutic evolution of a 1-year-old female child diagnosed with Down syndrome and treated at the Physiotherapy Teaching Clinic. This is a case study conducted through a complete evaluation involving anamnesis, postural analysis, joint tests, muscle strength assessment, anthropometric measurements, primitive reflexes, and application of the Alberta Infant Motor Scale (AIMS), which indicated a three-month motor delay in relation to chronological age. The therapeutic plan was structured focusing on early stimulation techniques, sensory integration, cervical and trunk control exercises, rolling training, facilitation of motor development, and play activities to promote engagement and functional response. Throughout the follow-up, significant progress was observed, such as improved trunk control, greater stability in sitting, initiation of independent lateral rolling, increased joint range of motion, and better response to sensorimotor stimuli. Reassessment also demonstrated improved motor coordination, overall strengthening, and development of functional skills, evidencing good family adherence and continuity of home-based stimulation. The findings of this study reinforce that early and systematic physiotherapy intervention significantly contributes to the motor development of children with Down syndrome, promoting greater autonomy, better postural organization, and advancement in neuropsychomotor acquisitions.